THE INFLUENCE OF EDUCATION AND SUPPORT GROUP BASED ON SELF-EFFICACY THEORY ON THE QUALITY OF LIFE AMONG CHRONIC KIDNEY DISEASE PATIENTS UNDERGOING HEMODIALYSIS: A NARRATIVE REVIEW - Dewi, Arie Kusumo; Tamara, Elok (Nurse and Holistic Care, 2022)
Background: Support group is a therapeutic process in a group that has the same problems to condition and provide reinforcement to the group or individual in the group according to the problem so as to achieve effective coping skills against the problem or trauma experienced and improve the patient’s quality of life. Objective: This review was to summarize and identify the current literature related to the influence of education and support group based on self-efficacy theory on the quality of life among chronic kidney disease patients undergoing hemodialysis. Methods: Data sources included two electronics databases: Google Scholar and Elsevier to search literature published between 2015 and 2022. A narrative review process was extract and analyze the data of all included studies. Result: The search found three articles that met the inclusion and exclusion criteria, including articles published in 2015 until 2022 and full-text form. Articles that meet the criteria are then analyzed narratively. Data search using keywords and criteria in the electronic data based above, resulted in 3 articles. From these articles, the interventions carried out, namely the Education, Support Group, Hemodialysis, Chronic Kidney Disease. Conclusion: The support group program has proven to be effective in increasing the patient’s ability to manage his condition and improve the quality of life.